Device Based Therapy for Treatment of Hypertension - Majumder, AAS; Ullah, M; Rahman, Z (Cardiovascular Journal, 2012)
DOI: http://dx.doi.org/10.3329/cardio.v4i2.10270 Cardiovasc. j. 2012; 4(2): 111-113